Comparative Analysis of Genetic Differences and Probiotic Characteristics of Human Gut-Dwelling Ligilactobacillus ruminis in Kashi, Xinjiang - YIN Tong, AN Meiling, LIANG Zhixuan, LU Yanzhuan, SUN Hailong, NI Yongqing (Shipin Kexue)
This study was focused on 16 strains of Ligilactobacillus ruminis isolated from fecal samples of healthy persons from different families in Kashi, Xinjiang. Genomic and phylogenetic analysis were conducted, and the in vitro probiotic characteristics of the strains were compared. Genomic analysis revealed that the average genome size, gene number, and GC content of the L. ruminis strains were 1.4 Mb, 1 374, and 43.55%, respectively. Notably, there were significant differences in the number of strain-specific genes, ranging from 3 to 886 (strain K646-58L had a notably higher number of specific genes compared with all other strains). In phylogenetic analysis, strains from the same family did not cluster together as closely based on their hosts’ genetic relatedness. The carbon source utilization experiments showed that the L. ruminis strains could utilize soybean oligosaccharides, cottonseed xylose, and maltodextrin, but not sorbitol or xylitol. The carbohydrate-active enzyme database (CAZy) annotated a large number of genes involved in polysaccharide substrate metabolism, such as the glycoside hydrolase (GH)1 and GH13 gene families. The 16 strains showed resistance to aminoglycosides but susceptibility to tetracyclines and chloramphenicol, which was not completely consistent with resistance gene prediction. All L. ruminis strains had high self-aggregation ability (> 50%) and good hydrophobicity (> 20%). Based on the genetic and phenotypic characteristics, L. ruminis had excellent probiotic properties, especially strains K227-6L and K645-5L. This study lays the theoretical foundation for the development and application of potential probiotic strains.